Harmony search algorithm for location-routing problem in supply chain network design - Misni, F.; Lee, L. S. (Academy of Sciences Malaysia, 2019)
The interdependence of facility location and vehicle routing has been recognized among the practitioners and researchers. The integration of these problems is more challenging in a supply chain network design problem. This paper considers a location-routing problem, which integrates the facility location problem and the vehicle routing problem. To effectively solved the problem, it is decomposed into three sub problems which are: location-allocation problem, multi-depot vehicle routing problem and multi-depot routing-allocation problem. The objective is to minimize the total operating facilities cost and the total travel distance cost between the depots and customers. A harmony search algorithm is proposed with several local optimisation approaches to further enhance the solution quality. The problem is tested with several benchmark dataset from the literature. The performance of the proposed algorithm is compared with other heuristic and metaheuristic approaches from the literature.